Komunikasi “Silent Treatment” Pada Hubungan Pasangan Generasi Milenial - Nawawi, Adelia Ismayana; Nawir, Rahmawati Hi. (JPS: Journal of Publicness Studies, 2025)
This study aims to describe and explain how millennials interpret the silent treatment in romantic relationships, whether as a form of self-protection, emotional control, or as a form of manipulation in relationships. This study used a qualitative descriptive method, because it focused on an in-depth understanding of the experiences and views of the research subjects. Data were collected through in-depth interviews with five respondents aged 29– 44 years (three women and two men) with different professional backgrounds. The results show that the silent treatment is interpreted differently by millennials: some use it as a strategy to calm themselves and prevent escalating conflicts, some see it as a form of emotional control in relationships, while others view the silent treatment as manipulative behavior that can damage communication. These findings confirm that the meaning of the silent treatment is strongly influenced by personal experiences, relationship dynamics, and an individual's ability to manage emotions.